DEVELOPING A UNIFIED FACIAL TISSUE THICKNESS MODEL FROM NEUROIMAGING DATA FOR SRI LANKA USING STATISTICAL ANALYSIS AND IMAGE PROCESSING TECHNIQUES - Batuwitage, Lochana T.; Jayawardena, Aparni; Sandamini, Himashi; Rajapakse, Roshan N.; Karunaratna, Damitha D.; Vidanapathirana, Muditha; Pallewatte, Aruna (International Journal of Research -GRANTHAALAYAH, 2017)
Facial soft tissue thickness (FSTT) is essential to forensic anthropologists for facial reconstruction- recreating a recognizable face from an unidentified skull and to plastic surgeons for treatment planning. Together with the age and sex of a person, the facial profile is related to facial soft tissue thickness, which is required for accurate facial reconstruction and recognition. Having such a facial profile in the national level is very important for a country since FSTT changes according to the geographical factors. In this paper we are presenting a review on literature associated with this topic describing the methods used for data collection, measuring FSTT and analyzing those values along with the method we are proposing to be followed in the research we are to conduct in the Sri Lankan context.